Variations in LC50 of some pesticides due to physico-chemical parameters and impact of sevin on neurosecretory cells of a fresh water snail, Thiara lineate - KD, Ahirrao; GD, Kedkar (Journal of Research in Biology, 2012)
Aquatic contamination by pesticides is arising as a result of their extensive use in agriculture and public health programmes. However, indiscriminate use of these pesticides for crop protection causes much damage to the aquatic fauna. The snail an aquatic fauna is economically important which serves as an intermediate host of various trematod parasites, which causes severe diseases to human being as well as domestic animals. The gastropod mollusc, Thiara lineata is a filter feeder at the secondary level of fresh water ecosystem. Hence felt necessary to study alteration in the LC50 and neurosecretion. The acclimatized, healthy, active and approximately same weight and sized mature adult and immature animals, groups of ten snails each were exposed (in Plastic troughs each containing 1 liter of water) to Organochlorine (Endosulfan), Organophosphate (Nuvacron), synthetic pyrethroids (Cymbush) and Carbamate (Sevin). The LC50 values for 24, 48, 72 and 96 hours were calculated. The physico-chemical parameters of water used for holding the animal had temperature between 26-28 0C , pH 7.1 to 7.3, total hardness 140 to 150 ppm and oxygen content of 5.6 to 7 ml/lit. The physico-chemical factors affecting the LC50 like temperature, pH, Salinity and Photoperiodism light and dark hours were studied. During the stress conditions neurosecretions are adversely affected . The snail are exposed to pre determined sub-lethal concentration of sevin(0.913 ppm) for 1,7 and 14 days, simultaneously controls were run. After exposure, It was found that the number of the neurosecretory cells ’A’ and ’B’ has suddenly discharged neurosecretory material. Neurosecretory material was found to be remaining accumulated in control snails